A Rasch Analysis of Teacher Understanding Regarding Project-Based Learning Models - Riskawati; Khaeruddin; Gurdi, Nurkhalifah; Akhila, A. Adinda; Tonang, Aisyah Putri; Putri, Chaela Amelya; Yunus, Sitti Rahma (Kasuari: Physics Education Journal (KPEJ), 2025)
Project Based Learning (PjBL) is one of the learning models that many teachers use in the learning process in this independent curriculum. Even so, the understanding and application of the PjBL model is still very varied, so this study was carried out to examine  the understanding and application of Project-Based Learning by teachers in South Sulawesi using quantitative methods and Rasch analysis. With PjBL gaining prominence in Indonesia's Merdeka Curriculum for developing 21st-century skills, challenges like uneven teacher readiness and resource limitations persist. The research aims to assess PjBL comprehension levels among teachers, examine demographic influences, and identify implementation barriers. Data were collected via a 26-item Likert-scale questionnaire administered to 300 teachers across primary, junior, and senior high schools. Rasch analysis confirmed the instrument's reliability (Cronbach's Alpha = 0.92) and validity. Findings revealed that female teachers, younger educators, and high school teachers demonstrated stronger PjBL understanding. However, practical application faced difficulties in project design, time management, and assessment. The study concludes that while conceptual knowledge exists, structural support and targeted training are needed for effective PjBL implementation. Recommendations include specialized professional development programs and policy interventions to address implementation gaps.